(3GdEUGHI aj JejjR GdUMGHIs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CMUi cd TF YOOG CeG HYO, aEf ef CTQa GdYdhe Yde GdMOjK GdfHhi s
(3BNQgG (B:s
(3hVHWg HaJM GdQG HYOgG jGA egehPI Ke CNQi SGcfI egedI Ydi GdUhGH GhdG BNQ GdSaQ GdChd ef GdEUGHg s
(3HChdgG hbajI ef GdSdWGf GdCTQa bGjJHGi Ydi eOQSJgs
(3ef fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B68 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B20 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs